Septal GABAergic inputs to CA1 govern contextual memory retrieval - Sans-Dublanc, Arnau; Razzauti, Adrià; Desikan, Srinidhi; Pascual, Marta; Monyer, Hannah; Sindreu, Carlos (Science advances, 2020)
The CA1 output region of the hippocampus plays an essential role in the retrieval of episodic memories. γ-Aminobutyric acid-releasing (GABAergic) long-range projections from the medial septum (MS) densely innervate the hippocampus, but whether septal inputs regulate memory expression remains elusive. We found that the MS to CA1 connection is recruited during recall of a contextual fear memory. Chemogenetic silencing of CA1-projecting MS neurons or septal GABAergic terminals within CA1 blocked memory retrieval. Photostimulation of septal GABAergic terminals in CA1 selectively inhibited interneurons. Abrogating septal GABAergic cells during retrieval disinhibited parvalbumin-rich (PV+) cells in CA1. Direct activation of CA1 PV+ cells impaired memory and prevented the induction of extracellular signal-regulated kinase/mitogen-activated kinase signaling in postsynaptic pyramidal neurons. Opposing disinhibition of hippocampal PV+ cells reversibly restored memory. Our data indicate that suppression of feed-forward inhibition onto CA1 by septal GABAergic neurons is an important mechanism in gating contextual fear behavior. - Septal GABAergic projections to CA1 interneurons support the recall of a past memory evoked by experience. - Septal GABAergic projections to CA1 interneurons support the recall of a past memory evoked by experience.